Faktor-faktor penentu repurchase intention pada produk shopping di e-commerce - Ajie Bayu Pangestu; Ari Setiyaningrum (Jurnal Manajemen Maranatha, 2023)
This study tries to investigate both the direct and indirect influence of privacy concern, innovativeness, and ease of use on repurchase intention through e-satisfaction as the mediating variable. The research model was examined within the context of shopping products in e-commerce involving 350 respondents. Sampling was carried out using a purposive sampling technique. PLS-SEM analysis with SmartPLS 3.0 software was utilized in the data analysis. The research findings indicate that privacy concern, innovativeness, and ease of use do not have a direct influence on repurchase intention, e-satisfaction was found to have an influence on repurchase intention. The results of the mediation test show that e-satisfaction is not proven to mediate the influence of privacy concern on repurchase intention, while e-satisfaction is proven to mediate the influence of innovativeness and ease of use on repurchase intention.